Reflections on an interview with the late Prof Maria Antonia Modolo - Gianfredi, V. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
The Author, now a Research Assistant at the Department of Public Health of the University of Milan, Italy, in the period she was a Resident of the School of Public Health of the University of Perugia, had the occasion to interview Prof Maria Antonietta Modolo, one of the most significant pioneers of Health Education and Health Promotion both in Europe and in this Country, and her mentor at that time. Prof Modolo, who recently passed away, in that occasion explained in detail all the goals of these disciplines, and the impact they can show on the life of the population of developed and developing countries, if applied within a robust public health framework.